North American Boreal Wildfire and Anthropogenic Emissin Impacts in the Lower Free Troposphere over the North Atlantic Region: observations at the PICO-NARE station - Fialho, Paulo (2013)
AGU Fall Meeting. San Francisco, California, 11-15 December 2006.